Pengembangan Aplikasi Al-Quran Untuk Membantu Hafalan Al-Quran Secara Mandiri Menggunakan Metode Tikrar - Adiama Septiara; Nurudin Santoso; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Indonesia is the largest memorizer of the Quran in the world with a total of 30 thousand people in 2010 and increasing every year. As the number of memorizers, the more memorization methods. One method of memorization that is often used is the method of repetition or tikrar method. Also with the growth of information technology today, many people tend to want things to be done easily and quickly, including in reading and memorizing the Al-Quran. Intending to help people memorize the Quran easily, then the author develop the Al-Quran tikrar mobile application. This application uses Tikrar memorization method which has 3 markers namely muraja`ah, tikrar and tilawah which are considered effective if used for memorization. Elisitation of needs in this system is based on the Al-Quran Tikrar from publisher Syaamil Quran. For Implementation, researchers using the Java programming language to develop the system. Then based on validation testing, this application gets a percentage of 100% which means the system has fulfilled functional requirements. While in the results of the usability test using the System Usability Scale (SUS), the average result was 58 which means its acceptable with an OK rating.